2023
DOI: 10.1371/journal.pdig.0000199
|View full text |Cite
|
Sign up to set email alerts
|

Proactive Contact Tracing

Abstract: The COVID-19 pandemic has spurred an unprecedented demand for interventions that can reduce disease spread without excessively restricting daily activity, given negative impacts on mental health and economic outcomes. Digital contact tracing (DCT) apps have emerged as a component of the epidemic management toolkit. Existing DCT apps typically recommend quarantine to all digitally-recorded contacts of test-confirmed cases. Over-reliance on testing may, however, impede the effectiveness of such apps, since by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…While previous research has already identified the need for actionable information [ 53 ], the information presented by DCT apps needs to be understood in the context of human action regulation and the influence of automated systems in human action regulation. A possible solution to support diagnosticity in DCT is so-called proactive contact tracing [ 54 ], which integrates more information sources and can potentially enrich DCT results.…”
Section: Discussionmentioning
confidence: 99%
“…While previous research has already identified the need for actionable information [ 53 ], the information presented by DCT apps needs to be understood in the context of human action regulation and the influence of automated systems in human action regulation. A possible solution to support diagnosticity in DCT is so-called proactive contact tracing [ 54 ], which integrates more information sources and can potentially enrich DCT results.…”
Section: Discussionmentioning
confidence: 99%
“…Various methods have been proposed to quantify the risk. The authors in [37,38,70] leverage the rich suite of individual-level features such as age and lifestyle habits as inputs to deep learning models [72] trained to predict the COVID-19 infectiousness of susceptible individuals. The work in [68] uses a sampling algorithm with Bayesian optimization and longitudinal case data to estimate the transmission rate of infected individuals in their households and at the locations they visited.…”
Section: Related Workmentioning
confidence: 99%